Investigations on thermal and environmental behavior of a 10-kW stationary diesel engine using nano-graphene-added preheated Karanja oil - Sonu Kumar Patidar; Hifjur Raheman (International Journal of Sustainable Energy)
The present study was conducted to investigate the performance and emission characteristics of four different fuel blends, viz. heated graphene oxide-added Karanja oil (HGKO), heated Karanja oil (HKO), Karanja oil (KO) and diesel in a 10-kW constant speed stationary diesel engine. Fuel properties of the prepared fuel blends were reported to be in line with diesel. The average ignition delay for KO-based fuels was found to be lesser (up to 3.36%) as compared to diesel due to the availability of fuel bourn oxygen. The addition of GO in HKO improved the cylinder gas pressure while reducing the peak HRR as compared to HKO at similar load conditions. The BTE and BSFC for HGKO were higher up to 11.81% and lesser up to 17.72%, respectively, with those of KO and HKO. The average CO and NOX emissions for HGKO were 11.28–40.91% and 2.73–10.76% lesser, respectively, over other tested fuel blends.